Emerging pollutants removal in full-scale biological treatment plants: A case study - Ulucan-Altuntas, Kubra; Manav-Demir, Neslihan; Ilhan, Fatih; Gelgor, Huseyin Baran; Huddersman, Katherine; Tiwary, Abhishek; Debik, Eyup (ELSEVIER, 2023)
Wastewater treatment plants (WWTPs) are the main source of emerging pollutants encountered in surface water, albeit existing standards apply to a very limited number of emerging compounds. This paper presents a case study on non-target analysis, performed on influent and effluent samples from the WWTPs in Kocaeli, Turkiye. The samples were concentrated through solid-phase extraction, followed by LC-MS/MS analysis to identify emerging compounds, typically found in wastewater and treated wastewater. The data obtained was evaluated based on wastewater characteristics and the flow rate of the selected WWTPs. The removal of detected emerging compounds was calculated and classified as - not removed, and partially removed. Our analysis showed pharmaceutics as the most prevalent detected compounds, with the highest level of removal efficiency. The study demonstrated the necessity for redesigning conventional WWTPs to reduce the potential escape of emerging pollutants, with potential accumulation and transformation into harmful by-products in the environment.
Keywords: Non -target analysis; Emerging compounds; Wastewater treatment plants; Biological wastewater treatment; PERSISTENT ORGANIC POLLUTANTS; MUNICIPAL WASTE-WATER; MEMBRANE BIOREACTOR; RISK; POPS; MICROPOLLUTANTS; CONTAMINANTS; OZONATION; TOXICITY; LEACHATE; Engineering; Water Resources